Perspectives on properties of the Human Genome Project - Kieff, F. Scott (Advances in genetics, 2003)
The groundbreaking work of modern genetics that culminated in the Human Genome Project has blazed new pathways in both science and law. As the assertion of property rights generally, and patents in particular, has become increasingly common surrounding the new products and processes of modern biotechnology, the transactions that must occur for downstream research and development to occur have shifted in important ways, in both academic and business settings. Perspectives on Properties of the Human Genome Project addresses the problems raised in this complex area under different regimes of laws and norms to offer hope and help as we wrestle to ensure optimal use of such essential innovations. This unique collection of authors, views, and topics is essential reading for academics, policy-makers, and practitioners in medicine, biology, sociology, management, ethics, law, and economics, and anyone else interested in gaining perspective on the broad interface between biotechnology and property. * Represents diverse views interwoven into a coherent dialogue * Includes contributions from the leading thinkers in the field * Explores the legal ramifications, in terms of property rights and patents, of the scientific developments arising from the work on the Human Genome Project.